Inhibition of VEGF and Angiopoietin-2 to Reduce Brain Metastases of Breast Cancer Burden - Bohn, Kaci A.; Adkins, Chris E.; Nounou, Mohamed I.; Lockman, Paul R. (Frontiers in Pharmacology, 2017)
For metastases in the central nervous system, angiogenesis enhances metastatic potential and promotes progression. Primary factors which drive vessel growth are VEGF and angiopoietin-2. Preclinical models show inhibition of either factor reduces metastases spread and inhibits growth. This work sets out to answer two questions in a preclinical mouse model. First, whether the combined inhibition of VEGF and angiopoietin-2, reduces passive permeability and limits drug uptake into brain metastases; and second, whether this inhibition reduces metastases burden in brain. We observed combinatorial inhibition of VEGF and angiopoietin-2, decreased (p<0.05) angiogenesis and vascular branching in an aortic ring assay and decreased (p<0.05) endothelial wound closure times. Using a brain metastases of breast cancer model (induced by intracardiac injections of brain seeking MDA-MB-231Br cells or 4T1Br cells), we observed, similar to VEGF, angiopoetin-2 expression correlates to increased angiogenesis (p<0.05) and increased lesion permeability. To determine efficacy, animals were administered bevacizumab plus L1-10 (angiopoietin inhibitor) twice per week until neurological symptoms developed. Lesion permeability significantly decreased by ~50% (p<0.05) compared to untreated lesions, but remained ~25% greater (p<0.0%) than brain. In subsequent experiments, animals were administered similar regimens but sacrificed on day 32. The number of metastatic lesions developed was significantly (p< 0.001) reduced in the bevacizumab group (56%) and combination group (86%). Lesions’ size was reduced in bevacizumab treated lesions (~67%) and bevacizumab and L1-10 treated lesions (~78%) developing area < 0.5 mm2. In summary, combinatorial inhibition of VEGF and angiopoietin reduces lesion permeability and brain metastatic burden.